2021
DOI: 10.1039/d0nr07960j
|View full text |Cite
|
Sign up to set email alerts
|

Size-controlled nanocrystals reveal spatial dependence and severity of nanoparticle coalescence and Ostwald ripening in sintering phenomena

Abstract: Colloidal nanocrystals allow investigating sintering phenomena in supported catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 44 publications
3
26
1
Order By: Relevance
“…Recent work by Cargnello et al demonstrated that whole particle migration and coalescence could exist as the dominant restructuring mechanism in Pd/SiO2 catalysts during 800°C aging. 37 In the core@shell system, however, we observe the coexistence of Pd cores alongside dispersed halo sites after the first cycle of aging. This suggests that total particle migration and coalescence is not the dominant restructuring mechanism in core@shell architectures.…”
Section: Metastability Of Halo Sites In Pd@sio2mentioning
confidence: 77%
See 1 more Smart Citation
“…Recent work by Cargnello et al demonstrated that whole particle migration and coalescence could exist as the dominant restructuring mechanism in Pd/SiO2 catalysts during 800°C aging. 37 In the core@shell system, however, we observe the coexistence of Pd cores alongside dispersed halo sites after the first cycle of aging. This suggests that total particle migration and coalescence is not the dominant restructuring mechanism in core@shell architectures.…”
Section: Metastability Of Halo Sites In Pd@sio2mentioning
confidence: 77%
“…This is consistent with other works which have shown that the initial placement of active metal readily implicates thermal stability. 36,37 Pd and CeO2 continued to agglomerate with successive aging cycles. By the end of the fourth 800°C aging cycle, the Pd dispersion dropped over five times to 5.9%.…”
Section: Adverse Restructuring In Conventionally Prepared Pd/ceo2mentioning
confidence: 99%
“…As a result, nanomaterials are metastable, which is quite sensitive to ambient temperature. To decrease the free energy of the system, atoms on the surface of nanoparticles will experience structural rearrangement and relaxation as the environmental temperature increases [ 25 , 26 , 27 ]. Figure 5 shows the DSC analysis of Cu NPs utilized in the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with other studies, which have shown that the initial placement of active metals readily implicates thermal stability. 36,37 Pd and CeO 2 continued to agglomerate with successive aging cycles. By the end of the fourth 800 °C aging cycle, the Pd dispersion dropped over 5 times to 5.9%.…”
Section: ■ Results and Discussionmentioning
confidence: 99%